Simulation and experimental investigation of thermal performance of a miniature flat plate heat pipe - Boukhanouf, Rabah; Haddad, A. (Hindawi Publishing Corporation, 2013)
This paper presents the results of a CFD analysis and experimental tests of two identical miniature flat plate heat pipes (FPHP) using sintered and screenmesh wicks and a comparative analysis and measurement of two solid copper base plates 1mmand 3mmthick. It was shown that the design of the miniature FPHP with sintered wick would achieve the specific temperature gradients threshold for heat dissipation rates of up to 80W.The experimental results also revealed that for localised heat sources of up to 40W, a solid copper base plate 3mm thick would have comparable heat transfer performances to that of the sintered wick FPHP. In addition, a marginal effect on the thermal performance of the sintered wick FPHP was recorded when its orientation was held at 0∘, 90∘, and 180∘ and for heat dissipation rates ranging from 0 to 100W.